A clinical and experimental study of platelet function in chronic renal failure - Evans, E. P. (1972)
Coagulation and platelet function studies were performed on 24 normal subjects and 29 patients with chronic renal failure due to various causes. Thrombocytopenia was uncommon in the uraemic patients but there was reduced platelet retention in glass bead columns and platelet aggregation with adenosine diphosphate (ADP) and thrombin was slower and less complete than normal. The rate of platelet disaggregation in uraemic patients was significantly reduced. The abnormalities tended to be more severe in more uraemic subjects. In normal subjects no inter-relationships were observed between the various measurements of platelet activity. In patients there were significant interrelationships between the measurements of platelet aggregation with ADP and thrombin and between the measurements of aggregation and retention in glass bead columns. It is suggested that if a common pathway is involved in these reactions it is adversely affected in uraemia. Plasma coagulation defects were uncommon and present in only five of the uraemic subjects. Impaired prothrombin consumption apparently due to defective platelet function was present in half the patients but was not detected by a kaolin activation method. Although platelet coagulation function was activated during ADP aggregation and disaggregation in normal and uraemic subjects, it did not correlate in the latter with impairment of aggregation. It is suggested that aggregation and activation of platelet coagulant activity are not necessarily related aspects of platelet function. An effect of uraemic plasma on normal platelets was demonstrated by mixing experiments consistent with a humoral cause for the uraemic platelet defects.